MUSAQAH DAN MUZARA’AH - Nur'ain Harahap (Universitas Islam Negeri Sumatera Utara, 2015)
Cooperation in agriculture has existed in the community. This cooperation is in the form musaqah and muzaraah. This cooperation is motivated the fact that there are people who have a tree, but he was not able to take care of him, or have a farm, but he was unable to manage it. musaqah contract applies to plants, while muzara'ah force on the ground. Cooperation is done in order productive land and produce.